Bridging Faith and Pandemic Challenges: Examining the Role of Religious Leaders - Arifinsyah, Arifinsyah (UIN Sunan Kalijaga Yogyakarta, 2023)
Confronting the challenges posed by COVID-19 has given rise to a distinctive reality involving religious leaders acting as mediators, bridging the practices of devout followers with religious doctrines and government initiatives. This study explores the approaches adopted by religious leaders affiliated with the Religious Harmony Forum (FKUB) in Medan City to combat COVID-19. Employing a qualitative methodology with verstehen theory as the analytical framework, this research reveals that these leaders tackled the threats of COVID-19 by providing assistance and restructuring worship practices. Notably, their actions were guided by a commitment to community safety rather than strict adherence to religious doctrines. The prioritization of humanity over religious interests aligns with the government's efforts to address the pandemic. A noteworthy outcome is observed in communities previously marked by intolerance, as individuals, despite differing beliefs, unite in an everyday movement, fostering a culture of tolerance. Consequently, tolerance emerges as a humanitarian response catalyzed by the pandemic, underscoring its significance as a fundamental aspect of compassionate awareness during these challenging times.